Development and validation of a terrestrial biotic ligand model for Ni toxicity to barley root elongation for non-calcareous soils. (July 2015) - Lin, Yanqing; Di Toro, Dominic M.; Allen, Herbert E.
Abstract: A Terrestrial Biotic Ligand Model (TBLM) for Ni toxicity to barley root elongation (RE) developed from experiments conducted in sand culture was used to predict toxicity in non-calcareous soils. Ca 2+ and Mg 2+ concentrations and pH in sand solution were varied individually and TBLM parameters were computed. EC50 increased as Mg 2+ increased, whereas the effect of Ca 2+ was insignificant. TBLM parameters developed from sand culture were validated by toxicity tests in eight Ni-amended, non-calcareous soils. Additional to Ni 2+ toxicity, toxicity from all solution ions was modelled independently as an osmotic effect and needed to be included for soil culture results. The EC50s and EC10s in soil culture were predicted within twofold of measured results. These are close to the results obtained using parameters estimated from the soil culture data itself. Highlights: Model parameters developed for barley root elongation in sand culture. Mg 2+ activity affects barley root elongation; Ca 2+ and H + activity do not. Parameters used to predict results for experiments in eight soils. Soil culture EC50 and EC10 predicted within twofold of measured results. Abstract : Terrestrial Biotic Ligand Model parameters estimated from plant data in sand culture were validated by soil culture toxicity data.